First aid at workplace during the COVID-19 pandemic: Training, resources and personal protective equipments for appointed workers - Angelo SACCO; Gabriella NUCERA; Francesco CHIRICO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2021)
During the COVID-19 pandemic, first aid provision at workplace must maintain its high priority. Therefore, first aid training courses require specific organizational, environmental and individual measures to be carried out safely and to protect both trainers and trainees from the COVID-19 infection. Occupational stakeholders should revise the content of the training courses, as well as resources and personal protective equipments available to occupational first aid responders in the face of pandemic. In this commentary, the authors argue about the Italian legal framework on this topic and suggest to update the Italian law on first aid at workplace in the wake of most recent national and international guidelines for lay rescuers.